6 Applying a positive deviance framework to the prevention of sexual intimate partner violence in 30 low- and middle-income countries. (19th September 2017) - Metheny, Nicholas; Stephenson, Rob
Abstract : Statement of purpose: This study examines whether positive deviance to specific community norms is associated with experiences of sexual intimate partner violence (IPV) among women in 30 low- and middle-income countries. Methods/approach: Positive deviants are individuals who transcend community norms and obtain better health outcomes than their peers with similar resources. In the first-ever application of positive deviance to IPV, this analysis used 30 nationally-representative Demographic and Health Surveys (DHS) completed in 2010 or later and containing a domestic violence module. Currently-married women ages 15–49 interviewed as part of the domestic violence module (n=350, 794) were included. Respondents indicated their husbands ever committed sexual IPV, creating a binary outcome. Twelve theory-derived variables were created and aggregated to the Primary Sampling Unit (PSU) to create community-level norms. Multilevel modelling was used to examine the association between positive departure from community-level norms and individual experiences of sexual IPV. Subsequent analyses stratified countries by IPV prevalence and score on the Gender Inequality Index (GII). Results: Results show positive deviance from at least one community-level norm was significantly associated with not reporting IPV in all 30 countries. These effects vary considerably by country, country-level IPV prevalence, and GII score. Conclusions: Positive deviance to certain community norms is associated with not experiencing sexual IPV among women across low- and middle-income countries. The increased normativity of abuse in countries with higher scores on the GII and higher rates of IPV may explain the stronger association between positive deviance and sexual IPV in these contexts. Significance/Contribution to Injury and Violence Prevention Science: This study is the first to apply positive deviance to the study of IPV and identifies factors that may be used for the primary prevention of IPV. The social proof that these are already adopted by some members of a community indicate scale-up may be possible.